Dimensi Aksiologis pada Tata Letak Bangunan di Bali Berdasarkan Lontar Asta Kosala Kosali - Siswadi, Gede Agus; Dwiputri Maharani, Septiana (Sphatika: Jurnal Teologi, 2023)
Bali is unique in its traditions, culture, religious practices, and architecture. All of these are a legacy from generation to generation. The form of Balinese architecture is strongly influenced by the values that are always maintained to remain the identity and uniqueness of the Balinese people. This research aims to explore the value system that develops in Balinese society, with how the value system frames the various cultural diversity owned by Bali, including Balinese architecture. This research uses a qualitative descriptive method with a phenomenological approach. The results of this study show that Balinese design and architecture are strongly influenced by the concept of Tri Hita Karana, a concept in Balinese society as a process of maintaining balance and harmony between God, humans and nature. The concept of Tri Hita Karana is then applied in Balinese architecture in the form of Tri Mandala, which is three spaces that divide one yard. Balinese architecture in Lontar Asta Kosala Kosali is also influenced by the concept of Sanga Mandala as a form of application of the concept of Dewata Nawa Sańga. Then the axiological dimension in the building layout in Bali has religious value, eco-theological value, aesthetic value, and also cultural value. Then, the challenges of Balinese architecture in this era of globalization position that the concept and layout of buildings in Bali still use concepts and also philosophical values that develop in Balinese society, despite regional limitations, but the axiological dimension on a small scale can still be maintained.